Manipulation of the aquatic environment to optimize the natural spawning of sunu grouper (Plectropomus leopardus) in controlled tanks - M. Deni Feraro Mubarrak; Ima Kusumanti; Wiyoto Wiyoto; Ahmad Muzaki (Depik, 2024)
Aquaculture within culture techniques is needed to support the optimization of a number of juveniles which sunu grouper natural spawning techniques. To optimize the natural spawning of Sunu Grouper (Plectropomus leopardus) its is needed to know in details about the environment condition. Random design method by using several treatments consisted of one factor, temperature, and consisted of four treatments which are 26, 28, 30, and 32 which were repeated five times. Five steps were conducting start with the preparation, acclimatization of the eggs, stocking, and hatching of the eggs, and larval maintenance. Good quality feed is required to support gonad development and egg quality during brood stock-rearing. Environmental management of culture within culture techniques is needed to support the optimization of the number of juveniles. Temperature changes made by raising and lowering the temperature are a form of stimulation that trigger spawning to occur naturally.Keywords:aquacultureaquatic environmentsunu grouper